The Role of Impregnated Curtains in Adult Mosquito Control in Wad Medani Town - El Tayeb Hassan, Faisal; Mohammed Taha, Isam Eldin (مجلة الجزيرة للعلوم الصحية; مجلد 7 عدد 2 (2011), 2011)
The purpose of this small study trail is to identify the role of impregnated curtains in controlling adult mosquitoes. The success of this study will solve all problems facing the insecticide house residual spraying mainly mosquito resistant to insecticides, high cost of insecticides and spraying operations and spraying refusals. The study was made in north-east of Wad Medani town in three houses facing permanent mosquito breeding ponds. Three rooms in three adjacent houses 50 meters from the breeding ponds were selected for the study. One room was treated with residual insecticide, the second room with impregnated curtains and the third room was left without intervention as control. The study period covered all the rainy season (15 / 7 – 15/ 10/ 2009) and the results showed that  high larvae count in the ponds, zero adult mosquito in room 1 and room 2 and high density of adult mosquitoes in room 3.The study recommended further study if this trial is recommended to be implemented in a large scale.